Adding Postal Follow-Up to a Web-Based Survey of Primary Care and Gastroenterology Clinic Physician Chiefs Improved Response Rates but not Response Quality or Representativeness. (September 2015) - Partin, Melissa R.; Powell, Adam A.; Burgess, Diana J.; Haggstrom, David A.; Gravely, Amy A.; Halek, Krysten; Bangerter, Ann; Shaukat, Aasma; Nelson, David B.
This study assessed whether postal follow-up to a web-based physician survey improves response rates, response quality, and representativeness. We recruited primary care and gastroenterology chiefs at 125 Veterans Affairs medical facilities to complete a 10-min web-based survey on colorectal cancer screening and diagnostic practices in 2010. We compared response rates, response errors, and representativeness in the primary care and gastroenterology samples before and after adding postal follow-up. Adding postal follow-up increased response rates by 20–25 percentage points; markedly greater increases than predicted from a third e-mail reminder. In the gastroenterology sample, the mean number of response errors made by web responders (0.25) was significantly smaller than the mean number made by postal responders (2.18), and web responders provided significantly longer responses to open-ended questions. There were no significant differences in these outcomes in the primary care sample. Adequate representativeness was achieved before postal follow-up in both samples, as indicated by the lack of significant differences between web responders and the recruitment population on facility characteristics. We conclude adding postal follow-up to this web-based physician leader survey improved response rates but not response quality or representativeness.